1995
DOI: 10.1002/mrd.1080420111
|View full text |Cite
|
Sign up to set email alerts
|

Further indications of the multicomponent nature of the acrosome reaction‐inducing substance of human follicular fluid

Abstract: Human follicular fluid (hFF), which has been treated with either unspecific proteases or dextran-coated charcoal (DCC) to remove proteins and/or steroids, cannot successfully induce the acrosome reaction (AR). After the removal of steroids, AR-inducing activity can be restored to hFF by supplementation with exogenous progesterone, but only in the presence of intact protein. Gel filtration experiments with 3H-progesterone-labelled hFF showed elution of the radioactive signal in the high molecular weight range, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…This study demonstrates that, even though the chemotactic activity of FF is retained after charcoal treatment, the apparent hyperactivation-causing activity is eliminated by this treatment. Since charcoal removes the steroid constituents of FF (including progesterone) [19], it can be concluded that the hyperactivation stimulated by FF is caused by a steroid constituent in the fluid, most likely progesterone. Our results and conclusion are in agreement with those of others [21,32] who found that sperm incubation with FF results in hyperactivation, unlike incubation with charcoal-treated FF or steroid-free plasma medium.…”
Section: Progesterone In Ff Appears To Be the Reason For The Hyperactmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrates that, even though the chemotactic activity of FF is retained after charcoal treatment, the apparent hyperactivation-causing activity is eliminated by this treatment. Since charcoal removes the steroid constituents of FF (including progesterone) [19], it can be concluded that the hyperactivation stimulated by FF is caused by a steroid constituent in the fluid, most likely progesterone. Our results and conclusion are in agreement with those of others [21,32] who found that sperm incubation with FF results in hyperactivation, unlike incubation with charcoal-treated FF or steroid-free plasma medium.…”
Section: Progesterone In Ff Appears To Be the Reason For The Hyperactmentioning
confidence: 99%
“…Progesterone as well as other steroids was removed from FF by adding dextran-coated charcoal, essentially as described by Fehl et al [19] with some minor modifications. Briefly, FF (500 l, 10 times diluted with PBS) was incubated with 250 l dextran (0.05%)-coated charcoal (0.5%) for 3 h at 4ЊC with rotation.…”
Section: Progesterone Removal From Ffmentioning
confidence: 99%
“…1989), thus being a possible physiological stimulus for the spermatozoon during transit in the female genital tract and at the moment of oocyte fertilization. In the female genital tract, it is found in a protein‐bound form (Fehl et al. 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, when spermatozoa are stimulated only with P, higher doses of the steroid (1 mM) are needed to stimulate the low affinity P receptor. Therefore, human acrosome reaction can be induced by micromolar P concentrations (19), but when the steroid is combined with CBG, a solution of CBG þ P at a nanomolar concentration is enough to elicit the AR (20).…”
Section: Figurementioning
confidence: 99%